Pediatric case of presacral ganglioneuroma: diagnostic considerations and therapeutic strategy - Saloua Ammar; Taycir Cheikhrouhou; Mohamed Jallouli; Rahma Chtourou; Sahla Sellami; Hayet Zitouni; Riadh Mhiri (SpringerOpen, 2021)
Abstract Background Ganglioneuroma (GN) is an uncommon tumor belonging to the neuroblastic tumors group and is often localized in the posterior mediastinum, retroperitoneum, and adrenal gland. Presacral (PS) location is extremely rare. Its management remains a challenge. Case presentation A 4-year-old child presented to our department for an isolated abdominal mass. Para-clinical exams concluded to PSGN. Subtotal surgical excision was performed through an anterior transperitoneal approach. The size of the residual tumor did not progress after the 6-year follow-up period and the patients were asymptomatic. Conclusions GN should be considered in the case of soft tissue presacral masses in pediatrics. Subtotal resection seems sufficient in case of an extension to the sacrum with low morbidity. The residual tumors are still stable and the prognosis seems conserved. Further, long-term follow-up in large studies is needed to confirm these findings.